Recycling trachyte waste from the quarry to the brick industry: Effects on physical and mechanical properties, and durability of new bricks. (30th March 2018) - Coletti, Chiara; Maritan, Lara; Cultrone, Giuseppe; Dalconi, Maria Chiara; Hein, Anno; Molina, Eduardo; Mazzoli, Claudio
Highlights: Trachyte waste represents an excellent alternative temper for brick production. Trachyte used as temper improves the physical and mechanical properties of bricks. Recycling waste may reduce requirements for raw materials currently exploited. Abstract: This work examined the possibility of recycling trachyte waste as temper for preparing new types of bricks, thus reducing disposal costs and requirements for increasingly vulnerable raw materials, ultimately reducing production costs. The influence of the waste addition was studied by determining the petrographic and physical characteristics of fired bricks, in order to assess their aesthetic and mechanical features. Alkali feldspars in trachyte turned out act as fluxing agents, favoring partial melting of the matrix. Textural and mineralogical analyses revealed a considerable increase in the number of connections among minerals, extensive re-crystallization of the matrix, and an overall increase in compactness, not only with increasing firing temperatures but also increasing trachyte contents. The physical and mechanical properties of all samples were comparable with those of traditional bricks, showing that the addition of trachyte confers sufficient technical features already at 900 °C, allowing further reduction of production costs by lowering firing temperatures.